Análise da correlação entre rugosidade e viabilidade celular em ligas de titânio - Trevilato, Renato (2024)
The interaction between biomaterials and cells is highly influenced by surface characteristics, particularly roughness and wettability, which are crucial factors for the viability of biocomponents. This study evaluated roughness parameters, such as average roughness (Ra), skewness (Rsk), and kurtosis (Rku), as well as wettability, varying droplet volume and adjustment methods, and the viability of fibroblasts and pre-osteoblasts on bioactive surfaces. Initially, Ti-6Al-4V ELI alloy samples machined at low feed rate (f = 0.038 mm), high feed rate (f = 0.198 mm), and polished were assessed for roughness, wettability, and fibroblast viability (L929). Subsequently, commercially pure titanium (grade 4), Ti-6Al-4V ELI, and Ti-12Mo-6Zr-2Fe (TMZF) alloys, also machined at low feed rate and polished, were characterized and tested for pre-osteoblast (MC3T3-E1) viability. The results highlighted the significant impact of surface finishing. Low-feed machined surfaces exhibited hydrophilic tendencies (θ < 90°), whereas polished surfaces demonstrated hydrophobic behavior (θ > 90°). Neither adjustment methods nor droplet volume variations significantly affected outcomes. Fibroblast assays indicated greater viability on low-feed machined surfaces. At the same time, TMZF alloy samples showed the best results for pre-osteoblasts, despite no significant differences in roughness or wettability among the alloys. These findings underscore the critical role of surface finishing in optimizing biomaterials for implants.